The impact of climate change on workplace safety and health hazard in facilities management: An in-depth review. (July 2022) - Lan, Tianxiang; Goh, Yang Miang; Jensen, Olivia; Asmore, Ashan Senel
Highlights: Reviewed facility management (FM) workplace safety and health (WSH) hazards. Pesticide exposure, vector-borne disease risk to increase with climate change. Identified gaps in the literature on FM-WSH hazards related to climate change. Proposed research agenda for studying climate change impacts on WSH hazards. Abstract: The impacts of climate change on workplace safety and health (WSH) have not been thoroughly explored. Furthermore, the existing literature has not focused specifically on the Facility Management (FM) industry despite being prone to WSH accidents and climate change impacts. This study reviews the current knowledge on WSH hazards in the FM industry and investigates how such hazards may worsen with climate change. An initial finding from the review was that the academic understanding of the scope of FM is fragmented, such that the terms used to categorise FM jobs are highly inconsistent across studies. Therefore, we propose a preliminary consolidated typology of FM jobs as a framework for the study. In addition, the review showed that 1) studies on climate change impacts on WSH ("CC-WSH literature") have predominantly focused on heat hazards. 2) Existing WSH hazards in FM jobs such as pesticide and disease vector exposure are expected to worsen under climate change in the CC-WSH literature. 3) Other hazards in the FM industry like exposure to bioaerosol, soil-borne pathogen, UV radiation, disinfectants and legionellosis may also worsen with climate change, but have received limited coverage in the CC-WSH literature. With the above findings, this study calls for more research on non-heat WSH hazards induced by climate change. It also calls for the development of a systematic quantitative risk assessment framework for climate-induced WSH risks. Lastly, this study highlighted the need to establish a consensus on the scope and terms used for the jobs in the FM industry.